(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2023)
The consumers are very much concerned about food safety. To ensure safe food for the consumers, it is essential to follow the pre harvest interval (PHI) of pesticides. Therefore, in order to ascertain the pre-harvest interval of fenitrothion and diazinon in hyacinth bean in the environmental conditions of Bangladesh, this study was started. The chosen organophosphorus insecticides (fenitrothion and diazinon) were sprayed with the recommended dose (1.5 ml/L of water) in a field trial at the Entomology Division of BARI, Gazipur. At 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, and 12 days after spray (DAS), samples were taken. The Gas chromatography (GC) with a Flame Thermionic Detector (FTD) was used to quantify the residues after the samples were prepared using a modified Quick, Easy, Cheap, Effective, Rugged and Safe (QuEChERS) extraction method. Fenitrothion residue was found up to 8 DAS, and at 7 DAS (0.018 mg/Kg), the level of residue was above the MRL. At 8 DAS, the fenitrothion residue was 0.007 mg/kg, which was below MRL. Pre-harvest interval (PHI) for fenitrothion was determined at 8 DAS, and no residue was found after 9 DAS. Diazinon residue was found up to 9 DAS, with the level of residue above the MRL at 8 DAS (0.016 mg/Kg). At 9 DAS, the diazinon residue was 0.007 mg/kg, which was below MRL. Pre-harvest interval (PHI) was determined for diazinon at 9 DAS, and as of 10 DAS, no residue was found. Asian Australas. J. Biosci. Biotechnol. 2023, 8 (2), 30-37